Numerical investigation of the seismic detectability of carbonate thin beds in the Boom Clay formation. Issue 1 (6th April 2016) - Carcione, José M.; Gei, Davide
Abstract: The present study evaluates the capacity of the Boom Clay as a host rock for disposal purposes, more precisely its seismic characterization, which may assess its long-term performance to store radioactive wastes. Although the formation is relatively uniform and homogeneous, there are embedded thin layers of septaria (carbonates) that may affect the integrity of the Boom Clay. Therefore, it is essential to locate these geobodies. The seismic data to characterize the Boom Clay has been acquired at the Kruibeke test site. The inversion, which allowed us to obtain the anisotropy parameters and seismic velocities of the clay, is complemented with further information such as log and laboratory data. The attenuation properties have been estimated from equivalent formations (having similar composition and seismic velocities). The inversion yields quite consistent results although the symmetry of the medium is unusual but physically possible, since the anisotropy parameter ϵ is negative. According to a time-domain calculation of the energy velocity at four frequency bands up to 900 Hz, velocity increases with frequency, a behaviour described by the Zener model. Then, we use this model to describe anisotropy and anelasticity that are implemented into the equation of motion to compute synthetic seismograms in the space–time domain. The technique is based on memory variables and the Fourier pseudospectral method. We have computed reflection coefficients of the septaria thin layer. At normal incidence, the P -wave coefficient vanishes at specific thicknesses of the layer and there is no conversion to the S wave. For example, calculations at 600 Hz show that for thicknesses of 1 m the septarium can be detected more easily since the amplitudes are higher (nearly 0.8). Converted PS waves have a high amplitude at large offsets (between 30° and 80°) and can be useful to identify the target on this basis. Moreover, we have investigated the effect of septaria embedded in the Boom Clay with several simulations, by considering a lateral partial continuity of the calcareous thin inclusions. The simulations with layers of calcareous material show continuity of the reflections even when the percentage of carbonate within the layer is very small (5–15 per cent), while for low content of the calcareous material, isolated septaria boulders generate diffraction events. We have also simulated the stacked seismic section obtained from processing of the field data. The matching between the field and synthetic sections is acceptable.